2002
DOI: 10.1136/oem.59.12.836
|View full text |Cite
|
Sign up to set email alerts
|

Self perceived work related stress and the relation with salivary IgA and lysozyme among emergency department nurses

Abstract: Aims: To assess and compare the self perceived work related stress among emergency department (ED) and general ward (GW) nurses, and to investigate its relation with salivary IgA and lysozyme. Methods: One hundred and thirty two of 208 (63.5%) registered female ED and GW nurses participated in the study. A modified mental health professional stress scale (PSS) was used to measure self perceived stress. ELISA methods were used to determine the salivary IgA and lysozyme levels. Results: On PSS, ED nurses had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 29 publications
10
69
2
Order By: Relevance
“…For example, university students undergoing exams [22] and prisoners [23] have been shown to have decreased levels; similarly, emergency nurses working under high stress conditions have been reported to have low sIgA levels [2]. The sIgA level is also known to decrease in a similar manner in people with a pessimistic outlook on life [24], thus studies are consistent in terms of chronic stress inducing decreased sIgA levels.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For example, university students undergoing exams [22] and prisoners [23] have been shown to have decreased levels; similarly, emergency nurses working under high stress conditions have been reported to have low sIgA levels [2]. The sIgA level is also known to decrease in a similar manner in people with a pessimistic outlook on life [24], thus studies are consistent in terms of chronic stress inducing decreased sIgA levels.…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, the long 16 h shift is apt to cause physical and mental exhaustion and disrupt the normal circadian rhythm [1]. Furthermore, many reports have confirmed that prolonged night schedule is highly stressful [2] [3] and associated with higher burnout rates [4] [5] and medical errors, but the precise physiological effects of a 16 h shift remain undetermined. Most assessments of fatigue rely on questionnaires that evaluate subjective fatigue severity while practical, objective evaluations are virtually nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme concentration was significantly (p<0,05) lower in the saliva sample taken before the exam in relation to the values obtained after the completion of all exams. Yang et al (17) have shown that the value of salivary lysozymes is related to mental health, which means that the value of salivary lysozyme stands in negative correlation to the level of experienced professional stress in emergency nurses in relation to general nurses.…”
Section: Lysozymementioning
confidence: 99%
“…Since stress shows the immunosuppressive effect, the level of secretory IgA (10,11,15) and lysozyme (16) release of catecholamine, which is difficult to track in the saliva because of low concentration, rapid degradation and hormone instability in the samples taken. It is also possible to use chromogranin A (CgA) (14,17) and enzyme α-amylase (14, 18) as a response of the sympatho-adrenomedullary system to stress, or as biomarkers of stress, as alternative indices of adrenergic activity, due to their stability in the saliva and reliability of the obtained values.…”
Section: Salivary Biomarkers Of Stressmentioning
confidence: 99%
“…Several studies repeatedly demonstrated relations between SIgA variations and psychological stress of students (Guo et al, 2002). Levels of SIgA are influenced by additional factors such as amount of water consumption (Backes et al, 2015), physical activity and physical challenge (Cieslak et al, 2003;Dwyer et al, 2010;Gleeson and Pyne, 2000), changes in biorhythms during work shift (Guo et al, 2002;Lac and Chamoux, 2003), time of the season, location, altitude above sea level and most of all by stress related to psychological challenge and persisting physical challenge (Cieslak et al, 2003;Cohen et al, 2001;Gleeson and Pyne, 2000;Guo et al, 2002;Hunter et al, 2011;Kidd et al, 2011;Powell et al, 2015;Yang et al, 2002). Two major branches of stress induction include autonomous nervous system and hypothalamus-adrenal gland-pituitary axis.…”
Section: Introductionmentioning
confidence: 99%